Educação a distância: o papel e a formação continuada do tutor presencial na rede privada - Lorena Andrade Costa (2020)
This paper presents the results of a Master’s investigation, which aimed to develop an overview of teaching in the distance modality in the last decade and understand the attributions and the role of the face-to-face tutor, who works in the undergraduate teaching courses and in the process of pedagogical mediation of a private institution, which offers online courses. From the outline of the acting scenario of this tutor, we analyzed the development and the implementation of a collaborative virtual space for continuing education to be offered to face-to-face tutors who work in the undergraduate teaching courses. To carry out this investigation, due to the qualitative character of the research, we made a case study through questionnaires and semi- structured interviews. In the first stage of the investigation, we made a preliminary survey through an online diagnostic questionnaire, in order to understand the general profile of the face-to-face tutors in the researched institution, as well as their relationship with the teaching and their context of education. We used a closed-ended questionnaire, consisting of 28 questions divided into four categories: general tutors’ data, academic background, pedagogical mediation and use of digital technologies. We sent the questionnaires to 42 face-to-face tutors, who work at the institution surveyed in November 2018, and we got 22 responses, that is, we had a significant sample of just over half of the professionals working in the research locus. In the second stage of the research, we interviewed four face-toface tutors who work in math, pedagogy and visual arts courses. Two tutors participated in the elaboration and implementation of the virtual formative space, the educational resource of this research. The results of the investigation showed that the face-to-face tutors perform the teaching function, because there is a commitment of the face-to-face tutoring in creating learning environments so that students are encouraged to build their own knowledge. However, at the beginning, the face-to-face tutors do not understand their roles in the pedagogical mediation in the Distance Education. Professionals pointed out that the initial and continuing teacher education do not meet the needs of tutoring practice, especially the education offered by the institution. According to the tutors, the initial and continuing teacher education are very out of context of reality that they experience in practice and present little dynamic configurations with excessive amount of theories that do not contribute to the practice of tutoring. We concluded that the construction and the development of the virtual formative space was consistent with the professional demands of tutors, because they had the opportunity to participate in all processes of elaboration and implementation of the education, thus surpassing the traditional training models pointed as limiting their professional development.